SPATIAL VARIABILITY OF INDOOR RADON CONCENTRATION IN SCHOOLS: IMPLICATIONS ON RADON MEASUREMENT PROTOCOLS. Issue 2 (31st October 2020) - Curguz, Z; Venoso, G; Zunic, Z S; Mirjanic, D; Ampollini, M; Carpentieri, C; Di Carlo, C; Caprio, M; Alavantic, D; Kolarz, P; Stojanovska, Z; Antignani, S; et al.
Abstract: The requirements about radon measurements in schools and public buildings included in most of the national and international legislations are generally restricted to all the rooms located at the ground floor and basement, assuming the soil beneath the building as the main source of indoor radon. In order to verify such an assumption for small buildings having at maximum two floors, a preliminary study was performed in 50 schools located in 15 municipalities of the Republic of Srpska. Results of this study suggest that a protocol requiring measurements at the ground floor only may be considered adequate. Due to the high radon spatial variability for rooms at the ground floor, it is preferable to require measurements in a high number of rooms (preferably in all of them) in order to assess the compliance with the reference level established by the legislation.